DEVELOPMENT OF MATHEMATICS LEARNING DEVICES WITH PROBLEM BASED LEARNING (PBL) MODELS ON MATERIALS FOR CONSTRUCTING FLAT SIDE SPACE - Nurbaiti; Sri Rezeki (UIR PRESS, 2021)
This study aims to produce mathematics learning tools in the form of Learning Implementation Plans (RPP) and Student Worksheets (LKPD) with Problem Based Learning (PBL) Models on the Material of Building Flat Side Spaces were tested valid. This study's development of learning tools used the development or R&D method using the 4-D model. The stages used in this research consist of three stages, namely: (1) the defining stage, (2) the design stage, and (3) the development stage. The data collection instruments in this study were the RPP validation sheet and the LKPD validation sheet. The data collection technique used was validation data from 2 Mathematics Education Lecturers, FKIP UIR, and two mathematics teachers at SMP Negeri 36 Pekanbaru. The analysis technique used is data validity analysis. The validity results of the RPP were 86.25% with a very valid category, and the results of the validity of the LKPD were 84.06% with a valid category. Based on this research, it was obtained that the mathematics learning device with the Problem Based Learning (PBL) Model on the Material of Building a Flat Side Space for Class VIII1 of SMP Negeri 36 Pekanbaru was valid